Digital marketing and service counseling at pak bagong restaurant purwantoro wonogiri - Raffli Farhan Dinata; Padmantyo, Sri (Institute of Computer Science (IOCS), 2025)
This community service initiative at Pak Bagong Restaurant in Purwantoro, Wonogiri, aimed to enhance the restaurant’s marketing, service quality, and facilities through a structured implementation process. The initial phase involved observing the current conditions of the business, followed by interviews with the restaurant owner to identify challenges. The project included three key stages: submitting a service proposal, executing the activities, and evaluating outcomes. Data collection relied on qualitative interviews to gain insights from respondents about their experiences and perceptions. The service improvements focused on upgrading the facilities, such as cleanliness, parking, and seating, to attract more customers. Additionally, digital marketing strategies using platforms like Instagram, WhatsApp, and Google Maps were implemented to improve visibility and competitiveness. Service enhancements included staff training on customer etiquette and hygiene practices, ensuring better customer interactions. The results demonstrated an increase in customer traffic, especially from institutions, contributing to higher revenue and job creation in the local community. However, challenges such as limited space remained. To ensure sustainable growth, it is essential to optimize digital marketing, expand facilities, diversify services, and regularly evaluate business performance.